Pemanfaatan Arang Aktif Batang Pisang (Musa Paradisiaca L) Sebagai Pengadsorpsi Toluen - Ardi, Ardi; Sitorus, Saibun; Alimuddin, Alimuddin (JURNAL ATOMIK, 2021)
ABSTRACT Test of activated carbon adsorption ability of banana stem waste (Musa paradisiaca L) on toluen has been carried out. Scanning Electron Microscopy (SEM) was used to characterize activated carbon to show the morphological differences in activated carbon after activation and before toluen adsorption using a UV spectrophotometer with variations in the time of adsorption and concentration. The optimum toluen adsorption time obtained on the adsorbent weight of 0.4 gram, the concentration of toluene 40 ppm was 45 minutes, then the absorbed toluene concentration was 61,75%. the adsorption capacity was 1,5438 mg/L and the optimum toluene concentration at 1 grams, 60 minutes adsorption time was 40 ppm. The concentration of toluene absorbed was 73,875%. Then the adsorption capacity was 0.07388 mg/L.